Employees’ work–family enrichment in leadership context: systematic review and meta-analytical investigation - Vadvilavičius, Tadas; Stelmokienė, Aurelija (Business: Theory and Practice, 2024)
The aim of this study is to systematically summarize and analyse the relationship between work-family enrichment/family-work enrichment and family-supportive supervisor behaviour. A systematic literature review procedure was applied to search and review articles in EBSCO Academic Ultimate (EBSCO), ScienceDirect, Web of Science, and Google Scholar. Fifteen papers were included. The systematic literature review mostly revealed the relationship between general work-family enrichment/family-work enrichment and family-supportive supervisor behaviour scores. To provide a summary of the results, a random effects model was employed for statistical analysis. The meta-analytic results revealed a moderate positive relationship between family-supportive supervisor behaviour and work-family enrichment, as well as between family-supportive supervisor behaviour and family-work enrichment. Furthermore, the results indicated that age and gender did not moderate these relationships. Recommendations for future research and practice are discussed. It is important to note that the main limitation of this review is the use of only general scores of family-supportive supervisor behaviour and work-family enrichment/family-work enrichment. This study is valuable because of providing summary of scattered data and reveals clearer relationship between family-supportive supervisor behaviour and work-family enrichment.